Burdeos. Gestos de contemporaneidad. - Carolina Bartalini (Cuadernos LIRICO)
The publication of Burdeos 1972 in 2013 is a crucial event. When this posthumous text came to light with the joint publication of the Diario de un canalla, it was thus added to the the autobiographical series of the author. Burdeos 1972 was written after La Novela Luminosa, hence one can assume that it is the last of Levrero’s stories, even if its space-time setting is thirty years before his trip and stay in Burdeos in 1972. Duplication, retrospection and recreation are the procedures Levrero uses in this feverish diary which reassembles the rules of the genre, and persists in writing the impossible : Recuperate the present by starting to tell the past in order to create an origin story—of his writing and of himself. If we write in order to remember and we remember in order to write, the paradox becomes a gesture of contemporaneity as presented by Giorgio Agamben « that relationship with time which adheres to it through a discrepancy and an anachronism ».